Водний режим і посухостійкість листків видів, форм та гібридів роду Salix L. - Kruglyak, Yu.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2010)
Water regime of leaves of willows species, forms and hybrids is defined by experimental way in laboratory conditions. On the basis of water keeping ability, water deficency indexes, water absorb ability and a stage of leaves retaining the most dry resistant plants are found. These are species: S. alatavica, S. capusii, S. caspica, S. cinerea, S. kangensis; hybrids: S. caspica × S. caprea, S. caspica × S. purpurea, S. purpurea × S. viminalis, S. purpurea × S. viminalis × S. caprea, S. × smithiana, S. viminalis × S. acutifоlia, S. viminalis × S. caprea. Willows, which have middle dry resistance are: S. acutifolia, S. purpurea, S. triandra. Not dry resistant willows are: S. eleagnos, S. integra, S. purpurea 'Angustifolia', S. purpurea 'Gracilis', S. tenuifolia, S. integra × S. acutifolia.